Elastic anisotropies, thermal conductivities and tensile properties of MAX phases Zr2AlC and Zr2AlN: A first-principles calculation. (February 2022) - Peng, Mingjun; Wang, Renfu; Wu, Yuejun; Yang, Ancang; Duan, Yonghua
Abstract: In this study, the mechanical stability, elastic properties, including single-crystal elastic constants, polycrystalline elastic modulus and elastic anisotropy, Debye temperatures, electronic properties, minimum thermal conductivities and tensile character of Zr2 AlC and Zr2 AlN were calculated by first-principles calculations based on density functional theory. The results showed that Zr2 AlX (X = C, N) are mechanically stable and anisotropic in elastic properties, and the degree of elastic anisotropy of Zr2 AlN is slightly greater than Zr2 AlC, and the sound velocities and minimum thermal conductivities of Zr2 AlC and Zr2 AlN along the [001] and [100] directions are also anisotropic. Moreover, the density of states (DOS) and charge density difference distributions showed that these Zr2 AlX have metallic-covalent-ionic mixed bonds. Finally, the calculated tensile properties along the [001] and [110] directions of these MAX phases showed that the tensile strength along the [110] direction is greater than that along the [001] direction. Highlights: The hardness and shear capacity are in a sequence of Zr2 AlN > Zr2 AlC. Zr2 AlC and Zr2 AlN are anisotropic in elastic modulus and tensile strength. Zr2 AlN has the higher [001]-direction and lower [110]-direction tensile strength. The formation enthalpies of competitive phases in Zr–Al–X system are calculated.